Politics, time and space in the era of shadow banking. Issue 6 (1st November 2016) - Bryan, Dick; Rafferty, Michael; Wigan, Duncan
ABSTRACT: In the wake of the Global Financial Crisis, there has been an understandable focus on the financial fragility and contagion aspects of shadow banking. This article argues that shadow banking is important for another set of reasons. It has been well established that shadow banking permits the transformation of assets and financial claims. It has also been established that fiscal and regulatory arbitrage occurs through shadow banking, and associated offshore financial activities. The article develops the argument that together these are transforming the times and spaces of modern finance, and directly challenging earlier spatio-temporal concepts of finance, and the regulatory/jurisdictional order built on them. The article suggests that the longer term significance of shadow banking may not just be its role in financial crisis, or even tax and regulatory arbitrage, but that it was here that innovative forms of capital were produced and generalised which transcended the spaces and times of earlier institutional, transactional and jurisdictional concepts of capital and wealth.